2020
DOI: 10.1103/physrevb.101.144436
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-induced critical exponents near a ferromagnetic quantum critical point in Mn1xCrxSi

Abstract: We report the observation of critical behavior in Mn 1−x Cr x Si (0 x 1) close to a T = 0 K quantum critical point, consistent with the Belitz-Kirkpatrick-Vojta (BKV) theory of disordered metallic ferromagnets. The critical exponents are in good agreement with the theoretical predictions of the BKV theory in the preasymptotic limit. A non-Fermi liquidlike behavior is seen down to 200 mK in the transport and thermodynamic properties around the critical concentration x C = 0.2. Quantum criticality and self-consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…4(a)]. On the other hand, our recent results in Mn 1−x Cr x Si [9] with FM QCP and non-mean-field exponents belong to the case of intermediate disorder [Fig. 4(b)].…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…4(a)]. On the other hand, our recent results in Mn 1−x Cr x Si [9] with FM QCP and non-mean-field exponents belong to the case of intermediate disorder [Fig. 4(b)].…”
mentioning
confidence: 81%
“…However, ferromagnetic (FM) QCP in clean metals is interrupted by a first-order (FO) transition at a tricritical point (TCP) [3][4][5][6][7]. On the contrary, studies demonstrated that an intermediate disorder suppresses the TCP and restores the QCP [7][8][9][10]. Nevertheless, strong disorder can also lead to the formation of locally ordered rare regions irrespective of the disordered bulk system [11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamic variables show unconventional behaviour [11] and some novel phases have been reported to emerge in the quantum critical region [9]. The transport properties of metals show deviations from the Fermi-liquid theory [12][13][14][15] and the formation of nematic fluid state [16,17] have been reported in the vicinity of quantum phase transitions. The quantum critical behaviour in different systems shows a universal behaviour depending on the dimensionality of the system and the order parameter [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, experimental signatures of the Griffiths phase are power laws with non-universal exponents 9 in thermodynamic responses, that are observed in many systems. 4,10 In general, disordered alloys close to a ferromagnetic QCP are recognized by unusual scaling behavior [11][12][13] with exponents that depend on the degree of disorder. 14 Note that QCPs in FM are rare, more often new phases emerge when T c gets suppressed.…”
Section: Introductionmentioning
confidence: 99%